PERBEDAAN KAPASITAS VITAL PARU ANTARA PEROKOK DENGAN BUKAN PEROKOK - Siti Fadlilah; Adi Sucipto; Eddy Aryanto; Sumarni Sumarni (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2020)
Cigarette smoke can interfere with the diffusion process so that O2 supply decreases into the tissues causing hypoxia and disturbed cell metabolism and CO2 increases in the blood and decreased vital lung capacity. The aim of this study is to determine the difference in lung vital capacity between smokers and nonsmokers. This type of research is a comparative quantitative study with cross sectional design. The population in this study were all male students of Nursing Study Program at one campus in Yogyakarta as many as 98 people. The sampling technique used was accidental sampling with a sample of 30 smokers and 30 non-smokers. Data collection tools using a questionnaire and measurement of lung vital capacity using a Spirometer. Bivariate analysis using Chi Square test. The vital lung capacity in the majority of smokers experiences mild restriction, as many as 17 people (56.6%). While the lung's vital capacity in the majority of Non-Smokers groups experienced mild restriction as many as 27 people (90%). The bivariate analysis results of the p-value of 0,000 (p <0.05). There is a difference in the vital lung capacity between smokers and nonsmokers in the Nursing Force Study Program Student at a University in Yogyakarta.